To the respectable body of gentlemen nominated by the publick voice as a committee, for managing the affairs of the inhabitants of this city, in the present exigency of our publick concerns . - Totten, Joseph, active 1774 (LLMC-digital (Series), 1774)
A protest against the actions of the committee.